Keserasian Alat Gali Muat dan Alat Angkut Dalam Meningkatkan Produktivitas Pengupasan Overburden Pada Pit Utara PT. Bara Prima Pratama Jobsite Batu Ampar, Kabupaten Indragiri Hilir, Provinsi Riau. - Roges Tomara Mahesa; Adree Octova; Yoszi Mingsi Anaperta (Journals Mining Engineering : Bina Tambang, 2021)
Abstract. In mining activities, production is an activity that produces minerals. In coal mining activities, there are two production operations carried out, namely overburden production and coal production, which to produce this production mechanical equipment is used which plays an important role in supporting the success of the production process. In the use of these mechanical tools, it is necessary to do precise calculations so that the capabilities of the tools can be used optimally and have a high level of efficiency to achieve production targets. PT. Bara Prima Pratama implements an open pit mining system with coal being mined. The mining method used is the Conventional Mining method, which is a mining method using digging and loading equipment and transportation equipment. The company is trying to meet its production targets with the aim of being able to meet domestic and export demands. In the overburden stripping activity, PT. Bara Prima Pratama uses a combination of mechanical equipment, namely a Excavator Doosan DX 500 LCA HD and Dump Truck Hino 500. For the compatibility of the work of the digging and loading equipment, a Match Factor value of 0.776 is obtained, which means that the digging-loading tool works less than 100% and the conveyance works 100% so that there is waiting time for the digging and loading equipment. After analyzing the Match Factor, the value is 1.03 so that the matching fleet calculation results are appropriate and the same. There is no waiting time for loading and unloading equipment or transportation equipment.